2019
DOI: 10.4467/2353737xct.19.023.10159
|View full text |Cite
|
Sign up to set email alerts
|

The flexural capacity of laminated veneer lumber beams strengthened with AFRP and GFRP sheets

Abstract: This paper presents the results of preliminary tests focused on the strengthening of laminated veneer lumber (LVL) beams with aramid fibre-reinforced polymer (AFRP) and glass fibre-reinforced polymer (GFRP) sheets. Edgewise bending tests were performed on elements throught 4-point loading. The following two types of strengthening arrangements were investigated: sheets bonded to the bottom face along the entire length of the element, and a U-shaped half-wrapped type of reinforcement. The reinforcement ratios of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
3
4
0
Order By: Relevance
“…Unreinforced beams tended to exhibit linear behavior with slight deviations in the curve at the end of the test. Similar behavior was observed for the bending of unreinforced LVL in the edgewise condition [9] and solid timber beams [41] with a relatively small cross-section height (up to 10 cm). This non-linearity, however, was not present when testing full-size (with the height of the cross-section being equal to 20 cm) LVL beams in an edgewise condition [32], where perfectly linear behavior was observed.…”
Section: Load-bearing Capacitysupporting
confidence: 74%
See 2 more Smart Citations
“…Unreinforced beams tended to exhibit linear behavior with slight deviations in the curve at the end of the test. Similar behavior was observed for the bending of unreinforced LVL in the edgewise condition [9] and solid timber beams [41] with a relatively small cross-section height (up to 10 cm). This non-linearity, however, was not present when testing full-size (with the height of the cross-section being equal to 20 cm) LVL beams in an edgewise condition [32], where perfectly linear behavior was observed.…”
Section: Load-bearing Capacitysupporting
confidence: 74%
“…The increased utilization of compressive strength of solid timber, glue-laminated timber, or laminated veneer lumber elements strengthened with FRP, as well as stepped-like failure for beams strengthened with FRP with low elongation at rupture, is expected behavior and has been reported in previous studies [7,9]. The beams reinforced with CFRP and GFRP sheets behaved similarly-in the figure, a linear part in the initial phase of the test is visible, followed by plasticization.…”
Section: Load-bearing Capacitysupporting
confidence: 69%
See 1 more Smart Citation
“…On the basis of the abovementioned results and the results of the tests presented in [2], it can be concluded that the effectiveness of strengthening LVL beams with CFRP sheets is higher than with the use of AFRP and GFRP sheets.…”
mentioning
confidence: 87%
“…The test results are a continuation of the work on reinforcing LVL beams with fiber-reinforced polymer materials. In other works [16,17], issues of reinforcing laboratory scale specimens by gluing aramid, carbon and glass sheets to the external surfaces of the components were raised.…”
Section: Introductionmentioning
confidence: 99%